Implications of Industrialized Building System on Labor Demand and Cost - Chen-Chen, Yong; Said, Rusmawati; Yee, Candy Gan Chin (Engineering International, 2018)
High dependence on foreign workers in the construction industry has been long known to be one of the contributing factors of labor demand issue. To address this problem, the implementation of new technology innovations, such as the Industrialized Building System (IBS) is suggested. The purpose of this research paper is to identify the implication of IBS on the labor requirement of the construction industry. In this paper, the authors used the survey-questionnaire method. The research involved data from the surveys completed by the contractors registered with the CIDB. Data Envelopment Analysis (DEA) has been applied, and the reliability of the DEA result has also been proved. The result obtained from the Data Envelopment Analysis (DEA), indicates that IBS contractors are still required to hire an unskilled worker to undergo the new technology transition. However, when the adoption rate of IBS gets higher, the issue of substantial influx and dependency on a foreign worker in the construction industry can be resolved gradually. Although the investment cost is high during the initial stage, IBS can help to reduce the construction cost in the long-term.
Keywords: IBS; Labor; DEA; Construction Industry